Ultrasonography and magnetic resonance imaging findings of rheumatoid arthritis-like arthritis in a patient with adult T-cell leukemia. Issue 6 (1st November 2016) - Kawashiri, Shin-ya; Nakamura, Hideki; Origuchi, Tomoki; Aoyagi, Kiyoshi; Kawakami, Atsushi
Abstract : A 43-year-old Japanese woman with adult T-cell leukemia (ATL) developed rheumatoid arthritis-like polyarthritis with dermatitis and skin erosion. Her rheumatoid factor and C-reactive protein results were positive. Musculoskeletal ultrasonography showed intra-articular and peritendinous power Doppler signal-positive synovitis. Plain magnetic resonance imaging showed synovitis of the above lesion and remarkable bone marrow edema/osteitis. She was diagnosed as having ATL-associated arthritis based on the invasion of ATL cells by skin biopsy at the arthritis lesion.